Phenotypic and biochemical responses of sugarcane cultivars to glyphosate application - Adriano, Rodrigo Cabral; Azania, Carlos Alberto Mathias; Pinto, Luciana Rossini; de Pádua Mathias Azania, Andréa Aparecida; Perecin, Dilermando [UNESP] (Springer Nature, 2013)
Sugarcane cultivars show varying degrees of herbicide susceptibility, with herbicide effects ranging from no injury to total plant eradication. In this study, phenotypic and biochemical responses to glyphosate were evaluated in three sugarcane cultivars. Herbicide tolerance of the three cultivars (IACSP93-3046, IACSP94-4004 and RB72454) was tested in a greenhouse experiment using a completely randomized design. The experiment consisted of four replications of treatments in a factorial arrangement of 3 cultivars × 6 glyphosate dosages (0, 1,440, 2,160, 2,880, 3,600 and 4,320 g a. e. ha-1). Intoxication symptoms, based on a percentage scale ranging from 0 (no injury) to 100 % (total plant death), and total chlorophyll content were recorded at 1, 2, 3, 6, 7, 10, 20 and 34 days after glyphosate application (DAA). Shikimate dehydrogenase and α-esterase isoenzyme assays were performed at 8, 24, 48, 72 and 144 h after application (HAA). Intoxication symptoms observed at 6 DAA ranged from 5 % at the lowest glyphosate dosage (1,440 g a. e. ha-1) to ~30 % at the highest dosage (4,320 g a. e. ha-1) across all cultivars. IACSP94-4004 and IACSP93-3046 were determined to be the most glyphosate-tolerant cultivars. Reduction in chlorophyll content was observed with high dosages of glyphosate at 6 DAA. The shikimate dehydrogenase banding pattern was generally conserved among cultivars and treatments, with the exception of the IACSP94-4004 cultivar, which showed alterations in the banding pattern of α-esterase after glyphosate application. © 2013 Society for Sugar Research & Promotion.
Keywords: α-Esterase; Glyphosate; Isoenzymes; Shikimate dehydrogenase; Sugarcane